FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN LABA PADA PERUSAHAAN KOSMETIK DAN RUMAH TANGGA INDUSTRI SUB SEKTOR DAN PERUSAHAAN RETAIL SERVICE PERDAGANGAN SUB SEKTOR TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Martini Martini; Monica Monica (JURNAL LENTERA AKUNTANSI, 2016)
ABSTRACT Profit Change is increase or decrease in profit company annually. The investors will know about increase or decrease profit which company reach than last year by seeing profit change so profit change is an indicator that can be used for rate performance company. This research was purpose to analyze the influence of Current Ratio (CR), Debt To Equity Ratio (DER), Return On Asset (ROA), and Total Aset Turnover (TATO) to Profit Change on company cosmetic and household manufacture sub sector and company retail trade service sub sector listed on the Indonesia Stock Exchange period 2012-2015.The population which used in this research were 29 companies cosmetic and household manufacture sub sector and company retail trade service sub sector listed on the Indonesia Stock Exchange and selected as many as 13 companies as a sample with purposive sampling method. Data analysis tool that this research used were the classical assumption test, multiple linier regression analysis, correlation analysis, coefficient of determination analysis and hypothesis testing.The result of this research was Current Ratio (CR), Debt To Equity Ratio (DER) and Total Asset Turnover (TATO) had no significant effect on the profit change and Return On Asset (ROA) had positive significant effect on the profit change.  Keyword : Current Ratio (CR), Debt To Equity Ratio (DER), Return On Asset (ROA), Total Aset Turnover (TATO) and Profit Change.